NURTURING ROOTS, CULTIVATING GROWTH: EMPOWERING LOCAL COMMUNITY DEVELOPMENT THROUGH BAMBOO EDU-TOURISM IN DESA CANDIREJO - B. T. Hasmanan, Zefanya
Poverty in Indonesia is a serious issue affecting millions of people, especially those living in rural areas. Income and education inequality are major factors exacerbating this problem. Educational data shows that many residents still have not achieved an adequate level of education. To address this poverty issue, a comprehensive community empowerment approach is needed, aiming to increase self-reliance and provide the necessary knowledge and skills, in line with the national development goals of creating an independent, advanced, and just society. Indonesia is rich in natural resources, including a diverse and versatile bamboo resource. However, not all of this bamboo resource potential has been optimally utilized. In Candirejo Village, Central Java, which is rich in bamboo, the residents still face high poverty levels due to their inability to optimize the potential of the bamboo resources. Therefore, a non-formal education and community empowerment approach in this village becomes very important. The proposed solution is the establishment of a bamboo education center focused on non-formal education. This facility will help increase the community's understanding and skills in utilizing bamboo as a resource. Additionally, bamboo processing facilities should also be provided to support the sustainability and quality of bamboo products. This will provide significant economic benefits for the local community while preserving important natural resources. Architecture plays a role in creating facilities that support community empowerment in Candirejo Village. These facilities should reflect the local cultural and natural resource wealth, enabling the community to learn, practice, and develop sustainable products. With the right design, the Candirejo community can improve their quality of life through education, cultural preservation, and sustainable utilization of bamboo resources.